Biofuel potential within chaetoceros species (bacillartophyceae) from coastal water of Pahang, Malaysia - Mohamad Anuar, Mohamad Fuad; Mohammad Noor, Normawaty; Khan Chowdhury, Ahmed Jalal; Yunus, Kamaruzzaman (2013)
Several marine diatoms have been known for their high lipid content. Chaetoceros is the largest genus of marine planktonic diatoms with approximately 400 species described. Lipid is important as primary storage for nutrient and essential for cell's growth and function. Nowdays, there are increasing in demands for alternative source of fuel with several attempts have been conducted to find the best ways for fatty acid collection and algae have been listed as potential source for lipid. This study was-aimed to analyze the production of fatty acids from marine algae Genus Chaetoceros. The results showed three species had been identified as Chaetoceros baculites, Chaetoceros anostomosans and Chaetoceros affinis var. willei. Chaetoceros baculites had higher growth rate compared to other species mention earlier. All species had more than 40o/o of total lipid detected during exponential phase of their growth. Based on accumulation, Chaetoceros baculites has higher lipid percentage than other species followed by Chaetoceros ffinis var. willei and lastly Chaetoceros anastomosans. This indicates that Genus Chaetoceros can be treated as potential sources biofuel industry in Malaysia.